The identification of sandfly species, from an area of Argentina with endemic leishmaniasis, by the PCR-based analysis of the gene coding for 18S ribosomal RNA - Barroso, Paola Andrea (2007)
The area around Río Blanco, in the Orán department in the north of the Argentinian province of Salta, is endemic for American tegumentary leishmaniasis. In an attempt to facilitate the identification of the Lutzomyia species in this area, sequences of the gene coding for the 18S ribosomal RNA (rRNA) of sandflies caught in a Shannon trap were explored, by a combination of PCR and analysis of restriction-fragment-length polymorphism (RFLP). The products from the PCR, which employed two primers developed specifically for this study (Lu.18S 1S and Lu.18S AR), were cloned into a commercial vector (pGEM-T Easy) so that their nucleotide sequences could be investigated. In the RFLP analysis, the products of single and double digestion with the AfaI and HapII restriction enzymes were separated by electrophoresis in 3% or 4% agarose. Taken together with the results of a morphological investigation of the flies, the resultant DNA fragment patterns were sufficient to identify most of the sandflies caught as Lu. neivai. Although two other species, Lu. cortelezzii and Lu. sallesi, were collected, they were relatively rare and only identified morphologically. A single digestion of the 18S-rRNA gene sequences with AfaI or HapII appeared sufficient and useful for the identification of Lu. neivai from the north of Salta province, and for several other Lutzomyia species.